(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
The objectives of this service activity are as follows: 1). Increase public understanding of the dangers of chikungunya mosquitoes and their solutions, 2). They were suppressing the spread of chikungunya mosquitoes through fogging and implementing the recommendations for the Eradication of Mosquito Nests (PSN) in the surrounding environment, 3). They are creating a drainage prototype to prevent chikungunya mosquito nests which can be used as examples for making the next prototype, 4). Increase community participation in suppressing chikungunya mosquito nests through the construction of drainage channels, 5). Improve a clean culture in maintaining the cleanliness of the drainage in the surrounding environment. The planned activities to be carried out are in collaboration with the local health center, and the Tasikmalaya city health office to reduce the number of chikungunya mosquito nests and, together with the community, build good drainage channels. The method of activity used is by bringing in experts from puskesmas, health offices, and unsil academics. Next, an approach is taken in solving problems through the 5W 1H strategy, which is solving problems from the questions: what, who, where, when, why, how. The solutions to the problems found in the field are as follows: 1). Provide a stimulus with the construction of a drainage system in accordance with the rules of the Public Works Department, 2). Cooperating with the Cigeureung Health Center by providing chemicals for fogging, 3). Counseling with the Health Center and the Tasikmalaya City Health Office regarding the dangers and solutions of diseases originating from chikungunya